PENGARUH GOODWILL, RESEARCH AND DEVELOPMENT (RnD), DAN INTELLECTUAL CAPITAL TERHADAP NILAI PASAR PERUSAHAAN - Imaningati, Sri; Sari, Novita (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2015)
This study aimed to examine the effect of goodwill, research anddeveopment (RnD) as well as the intellectual capital of the firm's marketvalue. Sampling method used is purposive sampling with the followingcriteria: (1) the Issuer is in the manufacturing industry that registered sharesare actively traded on the Indonesia Stock Exchange during the period from2009 to 2013, (2) the Issuer to publish a full annual financial statements forthe period December 31, 2009 - December 31, 2013, (3) the Issuer has arecord stock price at the close end of the year, (4) the Issuer has the value ofintangible assets is positive and (5) Has the complete data related to thevariables used in this study.Based on these criteria, of the 142 companies listed in the IndonesiaStock Exchange acquired 28 companies were used as a sample. Analyzerused to test the hypothesis of this study is multiple regression analysis.Theresult showed that (1) Goodwill negatively effect the market value of thecompany, (2) Research and development (RnD) positive effect about themarket value of the company and (3) Intellectual capital positive effect on themarket value of the company.